Le mouvement owéniste ou la formation du socialisme britannique (1800-1845) - Ophélie Siméon (Revue Française de Civilisation Britannique)
In the wake of a historiographical revival that began in the late 1960s and which has helped to rehabilitate “utopian” socialism as a theoretical and political school of thought in its own right, this article sets out to explore the origins, organisation and posterity of the first British socialist movement, also known as Owenism (1800-1845). It examines the paradox of a group that seemed apolitical at first glance, yet was nonetheless in touch with the political upheavals of its time, in connection with the desire to provide a set of definitive solutions to the “social question”. The delicate balance between the rejection of party politics, on the one hand, and militant action on the ground, on the other, will be explored through the study of structural tensions between Owen’s often paternalistic attitude and the democratic aspirations of many of his followers. The cross-analysis of three interdependent fields of action (workers’ rights, women’s rights and the suffrage issue) will help to carry out a political assessment of Owenism while pursuing a critical examination of the notion of “utopian socialism”.